Kazakhstan’s Infrastructure Programs and Urban Sustainability Analysis of Astana - Zauresh Atakhanova; Marzhan Baigaliyeva (Urban Science)
Astana, Kazakhstan’s capital city since 1997, gained from substantial public investment, achieving relatively low poverty, high income, and broad access to social services. Implementation of the state infrastructure programs, which were aligned with China’s 2013 Belt and Road Initiative, allowed Astana to become a transport hub, attract people, and improve housing conditions. However, our analysis indicates that Astana’s construction boom resulted in intensive use of financial and natural resources. Moreover, the loss of green and blue lands, accelerated during the implementation of the state infrastructure programs, raises concerns about the environmental impacts of infrastructure spending. As a result, our study highlights the importance of further research and broader stakeholder engagement for bringing Astana’s development path into closer alignment with the principles of sustainability. Specifically, Astana’s stakeholders should adhere to best practices of urban ecosystem preservation, managing sprawl, and efficient use of resources. Finally, integrating green and blue infrastructure in setting targets, allocating funding, and monitoring, improving, and reporting on traditional infrastructure initiatives becomes increasingly important for sustainable urban development.